Separation of Plaque-type Variants of Encephalomyocarditis Virus by Chromatography on Calcium Phosphate - Burness, A. T. H. (1967)
Encephalomyocarditis (EMC) virus (K-2 strain) was separated into two distinct peaks of optical density by chromatography on calcium phosphate, eluting at 0.17 and 0.31 m, respectively. The virus in these peaks could not be distinguished by infectivity (plaque-forming units), hemagglutinin activity, electron microscopic appearance, sedimentation coefficient, or base ratios. However, variants producing large plaques predominated in the first peak eluted, whereas variants producing small plaques were concentrated in the second peak. When plaque-purified large and small plaque variants were chromatographed individually, each gave a single peak eluting at 0.16 and at 0.43 m, respectively. However, one small plaque type isolated was eluted in the 0.17 m region expected for large plaque variants, and not with the bulk of the small plaque variants. There were indications that EMC virus (K-2 strain) could be separated into more than two peaks by use of selected elution gradients. The possibility that there may be a relationship between plaque size and point of elution from calcium phosphate is discussed.